Implementation by the prosecutor of the function of prosecution during evidence at the pre-trial investigation - Сухачова, І. (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2020)
The article is devoted to the study of the peculiarities of the prosecutor’s implementation of the function of accusation during the evidence in the pre-trial investigation. The author studies scientific approaches to the definition of the concept of «function» in criminal procedural law, established the features of the function of the prosecution. Based on the analysis of various theoretical positions of scientists, it is concluded that the prose- cutor in criminal proceedings performs a single function – the function of prosecution, which consists in establishing the event of a criminal offense, exposing the person who committed a criminal offense (its establishment, notification of suspicion), indictment, bringing charges, maintaining it in court, applying measures to ensure criminal proceedings. It is determined that all forms of participation of the prosecutor in evidence can be divided into two types: 1) direct forms of participation of the prosecutor in the collection and verification of evidence and 2) indirect forms covering the provision of instructions, warrants in criminal proceedings. The article examines the powers of the prosecutor in criminal proceedings. It is determined that the accusatory function is performed by the prosecutor both at the pre-trial and judicial stages of criminal proceedings. The powers of the prosecutor in the pre-trial investigation, which have the character of preparatory to the implementation of the function of the prosecution, and a number of powers of purely accusatory. It is concluded that the initial charge is realized by notifying the person of suspicion, and the final stage of the charge in the pre-trial investigation is the approval or drawing up of an indictment by the prosecutor, as well as motions for coercive measures of educational or medical nature.

Стаття присвячена дослідженню особливостей реалізації прокурором функції обвинувачення під час доказування на досудовому розслідуванні. Автором вивчено наукові підходи до визначення поняття «функція» в кримінальному процесуальному праві, встановлено особливості функції обвинувачення. На підставі аналізу різних теоретичних позицій учених зроблено висновок, що прокурор у кримінальному процесі здійснює єдину функцію – функцію обвинувачення, яка полягає у встановленні події кримінального правопорушення, викриття особи, яка вчинила кримінальне правопорушення (її встановлення, повідомлення їй про підозру), складанні обвинувального акта, пред’явлення обвинувачення, підтримання його в суді, застосування заходів забезпечення кримінального провадження. Визначено, що всі форми участі прокурора у доказуванні можна поділити на два види: 1) безпосередні форми участі прокурора у збиранні та перевірці доказів; 2) опосередковані форми, що охоплюють надання вказівок, доручень у кримінальному провадженні. У статті досліджено повноваження прокурора у кримінальному процесі. Визначено, що обвинувальна функція реалізується прокурором як на досудовій, так і на судовій стадіях кримінального провадження. Виділено повноваження прокурора на досудовому слідстві, які мають характер підготовчих до реалізації функції обвинувачення, та низку повноважень суто обвинувальних. Зроблено висновок, що первинне обвинувачення реалізується шляхом повідомлення особі про підозру, а заключним етапом обвинувачення на досудовому слідстві є затвердження або складення прокурором обвинувального акта, а також клопотань про застосування примусових заходів виховного або медичного характеру.
Реалізація прокурором функції обвинувачення під час доказування на досудовому розслідуванні
Keywords: prosecutor; function of accusation; evidence; procedural powers; criminal process; прокурор; функція обвинувачення; доказування; процесуальні повноваження; кримінальний процес